Exploring Aromatherapy: An Introductory Guide for BNYS Students - Sangeeth Somanadhapai (Medical Research and Its Applications Vol. 4, 2024)
The use of complementary and alternative therapies in conjunction with traditional medicine has become more popular these days. One complementary therapy that uses essential oils as the main therapeutic agent to treat a variety of ailments is aromatherapy. The use of complementary and alternative therapies in conjunction with traditional medicine has become more popular these days. One complementary therapy that uses essential oils as the main therapeutic agent to treat a variety of ailments is aromatherapy. Essential oils, which are claimed to be extremely concentrated compounds derived from flowers, leaves, stalks, fruits, and roots as well as distilled from resins, are the primary therapeutic agents used in aromatherapy. In just a few years, aromatherapy’s application in holistic health has grown significantly. Upon researching the literature on this therapy, it is discovered that a large number of studies have been conducted to investigate how this therapy affects the emotions and brain of humans.